Penerapan Intervensi Relaksasi Benson untuk Menurunkan Nyeri pada Pasien Systemic Lupus Erythematosus (SLE) - Widyaningrum, Salza Tri; Purwanti, Okti Sri; Utomo, Feri Cahyo (Journal of Telenursing (JOTING), 2025)
This study aims to analyze the application of benson relaxation techniques to reduce pain in Systemic Lupus Erythematosus (SLE) patients in Anggrek III room at Dr. Moewardi Hospital. The method used is a case study approach with interviews, document review and observation. The results showed that there was an effect of benson relaxation on reducing pain in Systemic Lupus Erythematosus (SLE) patients. The benson relaxation technique is implemented after analgesic administration with an implementation time of 30 minutes and is carried out every day for three consecutive days. In conclusion, patients become more relaxed and comfortable after benson relaxation is proven by a decrease in pain scale 8 to pain scale 2 with Numeric Rating Scale (NRS) measurement scale. Keywords: Benson Relaxation, Pain, Systemic Lupus Erythematosus (SLE)